Beyond RPE: The Perception of Exercise Under Normal and Ketotic Conditions - Faull, Olivia K.; Dearlove, David J.; Clarke, Kieran; Cox, Pete J. (Frontiers in Physiology, 2019)
Aim: Subjective perceptions of exercising exertion are integral to maintaining homeostasis. Traditional methods have utilised scores of ‘rating of perceived exertion’ (RPE) to quantify these subjective perceptions, and here we aimed to test whether this measure of RPE encompasses identifiable localised perceptions from the lungs (breathlessness) and legs (leg discomfort), as well as their corresponding measures of anxiety. We utilised the intervention of ketoacidosis (via consumption of an exogenous ketone ester drink) to independently perturb exercise-related metabolites and humoral signals, thus allowing us to additionally identify the possible contributing physiological signals to each of these perceptions, Methods: Twelve trained volunteers underwent two incremental bicycle ergometer tests to exhaustion, following ingestion of either an exogenous ketone ester or a taste-matched placebo drink. Cardiorespiratory measures, blood samples and perceived exertion scales were taken throughout. Firstly, two-way repeated-measures ANOVA were employed to identify the overall effects of ketoacidosis, followed by generalised linear mixed model regression to isolate physiological predictors contributing to each perception. Results: RPE was found to contain contributions from localised perceptions of breathlessness and leg discomfort, with no measurable effect of ketoacidosis on overall exertion. Leg discomfort and anxiety of breathing and leg discomfort were increased during ketoacidosis, and correspondingly contained pH within their prediction models. Anxiety of leg discomfort also encompassed additional humoral signals of blood glucose and ketone concentrations. Conclusion: These results indicate the presence of localised components of RPE in the form of breathlessness and leg discomfort. Furthermore, subjective perceptions of anxiety appear to result from a complex interplay of humoral signals, which may be evolutionarily important when monitoring exertion under times of metabolic stress, such as during starvation.